The first experience of distance learning in medical universities of Ukraine under the conditions of COVID-19 quarantine - N.L. Aryayev; L.E. Kaplina; L.I. Senkivska; V.V. Pavlova (Zaslavsky O.Yu., 2020)
The article deals with the first experience of distance learning in the discipline of pediatrics of 5th and 6th year students of the medical and international faculties of Odessa National Medical University, as well as in continuous professional development of doctors under the conditions of all-Ukrainian quarantine due to COVID-19 pandemic.